2022
DOI: 10.3390/pathogens11040386
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Group B Streptococcus in Pregnant Women and Their Neonates from a Sri Lankan Hospital

Abstract: We investigated the molecular epidemiology of Streptococcus agalactiae (Group B Streptococcus, GBS) from carriage in a cohort of pregnant mothers and their respective newborns in a Teaching Hospital in Sri Lanka. GBS vaginal carriage was assessed on pregnant mothers at pre-delivery (n = 250), post-delivery (n = 130), and from peri-rectal swabs of neonates (n = 159) in a prospective study. All colonizing, non-duplicate GBS isolates (n = 60) were analyzed for antimicrobial susceptibilities, capsular serotyping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The findings of the current study differ from a previous study done in Sri Lanka where Dissanayake et al [20] in 2015 reported penicillin sensitivity of 66.7%. Interestingly, a more recent study carried out in Sri Lanka by Sapugahawatte et al [21] in 2022 concluded similar findings to the current study, in that penicillin sensitivity was determined to be 100%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the current study differ from a previous study done in Sri Lanka where Dissanayake et al [20] in 2015 reported penicillin sensitivity of 66.7%. Interestingly, a more recent study carried out in Sri Lanka by Sapugahawatte et al [21] in 2022 concluded similar findings to the current study, in that penicillin sensitivity was determined to be 100%.…”
Section: Discussionsupporting
confidence: 89%
“…The mefA gene was found only in 4.4% of erythromycin-resistant GBS isolates in the current study; however, an association between the gene and the erythromycin resistance could not be determined. Sapugahawatte et al [21] in 2022 in Sri Lanka found that 6.6% of erythromycin-resistant strains possessed either ermA or mefA genes. Similar results were found in Zimbabwe (3.4%) [26] and South Africa (6%) [14] , while Poyart et al [28] also reported similar findings in France.…”
Section: Discussionmentioning
confidence: 99%
“…The similar diversity in CC1 has also been observed in Italy ( Piccinelli et al. 2015 ), Sri Lanka ( Sapugahawatte et al. 2022 ), and other regions of Japan ( Morozumi et al.…”
Section: Resultssupporting
confidence: 73%
“…According to the China Bacterial Drug Resistance Monitoring Network (CHINET), the resistance rates of S. agalactiae to clindamycin and erythromycin were as high as 59.7 and 74.5%, respectively, among 5,052 clinical strains between January and June 2022. The prevalence of S. agalactiae with MLSb phenotypes is increasing, and resistance mechanisms to clindamycin and erythromycin are multitudinous, including methyltransferases encoded by erm family genes, as well as mef and mre family genes encoding antibiotic efflux pumps (Gizachew et al, 2019;Meehan et al, 2021;Sapugahawatte et al, 2022). Fluoroquinolones are one of the important antibiotic classes for the treatment of S. agalactiae infection in adults, and mutations in gyrA and parC, encoding for DNA gyrase subunit and topoisomerase IV, respectively, reduce fluoroquinolone binding to their DNA targets, leading to enhanced tolerance to quinolones (Arias et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main serotypes associated with human pathogenesis are IA, IB, II, III, and V (Russell et al, 2017;Francois et al, 2019;Zhu et al, 2020), and the frequency of detecting serotypes varies based on geographical dispersion and other unknown factors. For example, serotypes III, V, and VI were dominant in Sri Lanka (Sapugahawatte et al, 2022), the frequency of serotype IA was higher than that of other serotypes in Brazil (Do et al, 2019), and serotype III was dominant in China (Cheng et al, 2020). Virulence factors include the α protein family (Alpha, Rib, Alp1 and Alp2/3; Furfaro et al, 2018;Paoletti and Kasper, 2019), serine-rich repeat protein (Srr; Seo et al, 2013;Lannes-Costa et al, 2021), hypervirulent GBS adhesin (HvgA; Tazi et al, 2010), laminin-binding protein (Lmb; Sridharan et al, 2019), Christie-Atkins-Munch-Petersen (CAMP) factor (Lang andPalmer, 2003), andpili (de Figueiredo et al, 2021a), all of which play important roles in infection type and severity.…”
Section: Introductionmentioning
confidence: 99%